6-Formylindolo[3,2-b]carbazole promotes proliferation of adipose-derived mesenchymal stem cells via activation of the Ahr–IL-6 signaling axis - Tran, Thanh Trung; Vu, Thi Tien; Tran, Kien Trung; Nakahama, Taisuke; Nguyen, Nam Trung (Bangladesh Journal of Pharmacology, 2025)
No abstract